A Convolution Approach on Partial Sums of Certain Harmonic Univalent Functions - Saurabh Porwal (International Journal of Mathematics and Mathematical Sciences)
The purpose of the present paper is to establish some new results giving the sharp bounds of the real parts of ratios of harmonic univalent functions to their sequences of partial sums by using convolution. Relevant connections of the results presented here with various known results are briefly indicated.